Waiting time distributions in a two-level fluctuator coupled to a superconducting charge detector - Máté Jenei; Elina Potanina; Ruichen Zhao; Kuan Y. Tan; Alessandro Rossi; Tuomo Tanttu; Kok W. Chan; Vasilii Sevriuk; Mikko Möttönen; Andrew Dzurak (Physical Review Research, 2019)
We analyze charge fluctuations in a parasitic state strongly coupled to a superconducting Josephson-junction-based charge detector. The charge dynamics of the state resembles that of electron transport in a quantum dot with two charge states, and hence we refer to it as a two-level fluctuator. By constructing the distribution of waiting times from the measured detector signal and comparing it with a waiting time theory, we extract the electron in- and out-tunneling rates for the two-level fluctuator, which are severely asymmetric.